PENGEMBANGAN BUKU AJAR BERBASIS SAKU PEMBELAJARAN MEMBACA PERMULAAN BAGI SISWA SD NEGERI LAMREH BANDA ACEH - Totok Bintoro; Musdiani Musdiani; Mardhatillah Mardhatillah; Siti Mayang Sari; Akmaluddin Akmaluddin; Nurul Zikri Filina (Jurnal Visipena, 2022)
A pocket and is practical to carry and read anytime and anywhere. Pocket books are printed media that are used in the learning process. Beginning reading learning for students is needed in preparing for the advanced reading stage. Beginning reading can be interpreted as students starting to recognize letters. The purpose of education is to make a person or student who has broad knowledge and good ethics and can be useful for the students themselves and can apply their knowledge in the community. This study aims to determine the feasibility of books as teaching materials and their effectiveness in improving the ability to read the beginning of the environmental material around the first graders of SD Negeri Lamreh. This research is a type of research and development research. The subjects of this study were the first-grade students of SD Negeri Lamreh. The techniques used to collect data are questionnaires, observations and learning outcomes tests. The data collected were analyzed using descriptive statistics in the form of percentages. The results of the study showed that the feasibility was at 96% validation results with 96% design details, 95% material, 100% language and 93% feasibility and practicality. The students' completeness in using pocket books for reading the beginning is 87%. Thus, it can be concluded that pocket books are suitable to be used as learning resources and the results of pocket books are effective for improving student learning outcomes in early reading. Abstrak Buku Ajar berbasis saku dan praktis dibawa serta dibaca kapan dan dimana saja. Pembelajaran membaca permulaan untuk siswa sangatlah dibutuhkan dalam mempersiapkan tahap membaca lanjutan. Membaca permulaan dapat diartikan dengan siswa yang berawal mula mengenal huruf. Tujuan pendidikan adalah menjadikan seseorang atau siswa yang mempunyai pengetahuan luas dan etika yang baik serta dapat berguna bagi siswa itu sendiri dan dapat menerapkan pengetahuannya dilingkungan masyarakat. Penelitian ini bertujuan untuk mengetahui kelayakan buku sebagai bahan ajar dan efektifitasnya dalam meningkatkan kemampuan membaca permulaan pada materi lingkungan sekitar siswa kelas I SD Negeri Lamreh. Penelitian ini merupakan jenis penelitian Research and Development. Subjek penelitian ini adalah siswa kelas I SD Negeri Lamreh. Teknik yang digunakan untuk mengumpulkan data adalah angket, observasi dan tes hasil belajar. Data yang terkumpul dianalisis dengan menggunakan statistic deskriptif berupa presentase. Hasil penelitian bahwa kelayakan berada pada hasil validasi 96% dengan rincian desain 96%, materi 95%, bahasa 100% serta kelayakan dan kepraktisan 93%. Ketuntasan siswa menggunakan buku saku membaca permulaan bernilai 87%. Disimpulkan bahwa buku ajar berbasis saku layak digunakan dengan efektif untuk meningkatkan hasil belajar siswa dalam membaca permulaan.